Hardgrove grindability index and approximate work index of sodium feldspar - Chairoj Rattanakawin (Songklanakarin Journal of Science and Technology (SJST), 2019)
The purpose of this research was to study the feldspar of Nopphitam District, Nakhon Si Thammarat Province, Thailand with emphasis on Hardgrove grindability and determination of the approximate work index. Feldspar samples were collected, prepared, and analyzed for their chemical composition. From the analysis of the alkaline metal oxides, all samples were characterized as sodium feldspar. The Hardgrove grindability test used a ball-race test mill. The Hardgrove grindability indices of these feldspar samples had an average of 46.25. Knowing the average Hardgrove index, a calculated work index of 12.88 kW/STPH was estimated using Aplan’s empirical formula. This average work index was less comparable to those of feldspar ores given in the literature. Therefore, the method of Berry and Bruce was used to determine the specific energy and approximate work index. By running a batch dry-grinding test in a rod mill, an average specific energy of 7.34 kW/STPH was determined using Bond’s formula with the reference work index of 11.25 kW/STPH. This specific value is limited to these test conditions: (1) 18x36 cm mill with material hold-up of about 0.08, media loading of about 0.4, and half interstitial filling and (2) each sample must be ground by 8 steel rods with dimensions of 3.5x35 cm each for 15 min. Under these conditions, the approximate work indices of various minerals can be rapidly estimated knowing the 80% passing size (μm) of both feed and product from rodmilling that conforms to the indicated conditions. For example, the approximate work index of Sam Ngao sodium feldspar was 11.03 kW/STPH. This work index was quite comparable to those acquired from various mill manufactures. To obtain more accurate values of sodium feldspar’s work indices, the time-consuming Bond procedure should be performed with a number of corrections for different milling conditions.